Pharmacogenetic strategies to mitigate cisplatin-induced ototoxicity in head and neck cancer: A cost-minimization analysis with the use of GSTP1 c.313A>G genotyping - Ligia Traldi Macedo; Vinicius Eduardo Ferrari; Ericka Francislaine Dias Costa; Gustavo Jacob Lourenço; Luciane Calonga; Arthur Menino Castilho; Carlos Takahiro Chone; Carmen Silvia Passos Lima (PLoS ONE, 2026)
Background Cisplatin is a cornerstone agent in the treatment of head and neck squamous cell carcinoma. Nonetheless, cisplatin is associated with significant ototoxicity, leading to substantial irreversible hearing loss. Pharmacogenetic testing offers a potential strategy to identify patients at risk, allowing for personalized treatment plans that could mitigate this adverse event and reduce related costs. Methods This study aimed to evaluate the economic impact of pharmacogenomic screening. A cost-minimization analysis was conducted using a decision-analytic model incorporating Bayesian inference through Metropolis-Hastings algorithm. Probabilities of ototoxicity were derived from existing literature. The costs of standard treatment were compared with those of a genotype-guided approach, assessing potential cost savings related to the need for audiological interventions. Results In 250 patients, the genotype-guided approach reduced the incidence of moderate-to-severe ototoxicity from 29% to 18% among low-risk patients while avoiding cisplatin in high-risk individuals. The total savings over 10 years were estimated at US$13,077.73 (Credible Interval US$11,026.07 to US$14,147.61), driven primarily by reduced costs for audiological interventions. The break-even point for cost-effectiveness was achieved when at least 275 patients were tested annually. Sensitivity analyses demonstrated that the cost savings remained robust under variations in patient volume and testing costs. Conclusions Implementing pharmacogenomic screening in the management of head and neck squamous cell carcinoma patients treated with cisplatin may offer significant economic benefits. Personalized treatment plans based on genetic risk for ototoxicity could potentially not only enhance patient-related outcomes but also contribute to more efficient use of healthcare resources. Prospective, randomized evaluations would be ideal to confirm these findings.